Phylogenetic and Genetic Distance Analysis of the Mangrove Worm (Namalycastis) Based on the 18S rRNA Gene Using in Silico Methods - Arielda Putri Aditya; Junardi Aditya; Wolly Candramila; Kartika Prabasari (Genetikawan Muda Indonesia, 2025)
Namalycastis is a polychaete worm that inhabits dynamic aquatic environments and exhibits high genetic and morphological variability. This study investigates the phylogeny of the genus Namalycastis through an in silico analysis using the 18S ribosomal RNA (rRNA) gene. This genetic marker is considered ideal as it combines conserved and variable regions, both essential for taxonomic and evolutionary analyses. The objective of this research was to examine the phylogenetic relationships and genetic distances among 12 species of the genus Namalycastis based on their 18S rRNA gene sequences. DNA sequences were obtained from the NCBI database and aligned using Clustal-W in MEGA XI software. Phylogenetic reconstruction was performed using the Neighbor-Joining method with 1000 bootstrap replications, applying the Kimura 2-Parameter (K2P) model. The results revealed that Namalycastis jaya shares a very close evolutionary relationship with Namalycastis abiuma, forming a monophyletic clade that is distinct from Namalycastis hawaiiensis. The genetic distances among N. jaya, N. abiuma, and N. abiuma group sp. indicate a close evolutionary affinity, whereas N. hawaiiensis displays greater genetic divergence from the other two species. Overall, this study demonstrates that the 18S rRNA gene is an effective molecular marker for identifying phylogenetic relationships among Namalycastis species. The findings also highlight the potential of in silico methods in elucidating evolutionary patterns within the genus Namalycastis.